Blowup Analysis for a Semilinear Parabolic System with Nonlocal Boundary Condition. (22nd November 2009) - Wang, Yulan; Xiang, Zhaoyin
Abstract : This paper deals with the properties of positive solutions to a semilinear parabolic system with nonlocal boundary condition. We first give the criteria for finite time blowup or global existence, which shows the important influence of nonlocal boundary. And then we establish the precise blowup rate estimate for small weighted nonlocal boundary.